2017
DOI: 10.1098/rsos.160957
|View full text |Cite
|
Sign up to set email alerts
|

Morphology captures diet and locomotor types in rodents

Abstract: To understand the functional meaning of morphological features, we need to relate what we know about morphology and ecology in a meaningful, quantitative framework. Closely related species usually share more phenotypic features than distant ones, but close relatives do not necessarily have the same ecologies. Rodents are the most diverse group of living mammals, with impressive ecomorphological diversification. We used museum collections and ecological literature to gather data on morphology, diet and locomoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
69
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 66 publications
1
69
2
Order By: Relevance
“…Congruent, complex scenarios were found for explaining echimyid cranium and mandible evolution (Monteiro et al., ; Perez et al., ; Tavares, Pessôa, & Seuánez, ; Tavares et al., ), as well as in the cranial and postcranial skeleton of Caviomorpha (Álvarez, Perez, & Verzi, ; Álvarez et al., ; Candela & Picasso, ; Morgan, ; Morgan & Álvarez, ; Morgan & Verzi, ). Differently from the pattern found in muroid lineages (Verde Arregoitia et al., ), ecological pressures along echimyid evolution did not overshadow phylogenetic components of external morphology because ecological specializations, although more concentrated during early diversification, emerged gradually during the phyletic diversification of this family. This was consistent with a relatively small disparification of echimyid skulls respective to other closely related caviomorph families (Octodontidae and Abrocomidae) that were exposed to more stringent environmental pressures during diversification (Verzi et al., ).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Congruent, complex scenarios were found for explaining echimyid cranium and mandible evolution (Monteiro et al., ; Perez et al., ; Tavares, Pessôa, & Seuánez, ; Tavares et al., ), as well as in the cranial and postcranial skeleton of Caviomorpha (Álvarez, Perez, & Verzi, ; Álvarez et al., ; Candela & Picasso, ; Morgan, ; Morgan & Álvarez, ; Morgan & Verzi, ). Differently from the pattern found in muroid lineages (Verde Arregoitia et al., ), ecological pressures along echimyid evolution did not overshadow phylogenetic components of external morphology because ecological specializations, although more concentrated during early diversification, emerged gradually during the phyletic diversification of this family. This was consistent with a relatively small disparification of echimyid skulls respective to other closely related caviomorph families (Octodontidae and Abrocomidae) that were exposed to more stringent environmental pressures during diversification (Verzi et al., ).…”
Section: Discussioncontrasting
confidence: 67%
“…As the species‐richest mammalian order, rodents show a wide range of morphological and ecological variation (Patton, Pardiñas, & D'Elía, ; Samuels & Van Valkenburgh, ). A recent study showed that a large amount of external morphological variation in this order were attributed to locomotory specializations with few phylogenetic components (Verde Arregoitia et al., ). This study, mainly on muroid lineages, did not clarify the association between morphology and locomotory habits in caviomorph families.…”
Section: Discussionmentioning
confidence: 99%
“…; Verde Arregoitia et al. ). Luzon is an oceanic island that began emerging as a continuously dry‐land area approximately 25 million years ago (Hall ).…”
mentioning
confidence: 99%
“…Regarding the animal recipient model, five out of the eight studies used mice, whereas the remaining three studies used rat models. Both rats and mice have been classified under the terrestrial locomotion category , and additionally, it has been reported that there are no statistical differences in functional motor recovery between rat and mouse animal models after cellular treatment for SCI . Therefore, our meta‐analysis demonstrated that even though there is heterogeneity present, the use of NSC/PCs from iPSCs has a significant benefit in the motor recovery.…”
Section: Discussionmentioning
confidence: 65%